APPLICATION OF STRETCHING TO STIMULATE THE HEALTH OF OLDER PRESCHOOL CHILDREN (Academicia Globe: Inderscience Research, 2022)
This article presents a meaningful description of stretching as a technology for preserving and stimulating the health of children. The features of the organization and conduct of stretching classes with children of older preschool age are considered.